The effects of two different HIIT resting protocols on children`s swimming efficiency and performance - Papadimitriou, K.; Savvoulidis, S. (Central European Journal of Sport Sciences and Medicine, 2020)
On children, HIIT program is being used by coaches as a way of rapid improvement. The values of the intervals vary from the target of the period. The study`s purpose was to find out if HIIT in different interval protocols improves children`s swimming performance. In the study participated 18 rookie swimmers (9 boys and 9 girls), aged 11.6 ±1.5. The HIIT protocol in both groups included the set of 2 * 4 * 17.5 m (freestyle and freestyle kick, respectively). The first group (HIIT 1) had a 10 sec interval while the second (HIIT 2) a 1 min between the HIIT reps. Swimmers performed in 35 m freestyle (35F) and 2 min free kick (2` FK) trials at maximum effort. The performance (T), the number of strokes (SN) and the stroke length (SL) were measured at 35F, the covered distance at 2' FK and the heart rate (HR), the rated perception of exertion (RPE) at 35F and 2` FK. Regarding the results, all parameters improved significantly (p = 0.01). The use of a 4-week swimming program with training 4 times per week, in which two were HIIT, improved children`s performance and efficiency in swimming. Intervals of 10 sec or 1 min did not alter the improvement.